KAJIAN PENERAPAN GOAL CONGRUENCE DALAM BERBAGAI PERSPEKTIF DAN AKTIVITAS USAHA - Heri Suseno; Nishnurtia Razak; Hanif Hanif (Jurnal Ilmiah Hospitality, 2022)
This study seeks to see the extent to which the application of the concept of congruence or goal congruence (goal congruence, abbreviated GC) in various perspectives and business activities to achieve the level of performance and goals set, by summarizing some of the results of previous research. How the implementation of the GC concept, what influences it and what novelties have been made, become the focus of research. GC in important management control achieved by the parties to achieve or the specified level of performance, harmonizing the goals of each individual with the various goals of the organization, or the goals of the scope of the community. Research on the application of GC is not only in a business organization, but also in several organizations and various groups, individuals and communities, business actors and the general public. The research method was carried out by reviewing 27 relevant literatures, originating from national and foreign authors and literature publishers from 1991 to 2021. The study using a systematic literature review (SLR) methodological approach shows that the application of GC does not only apply within the scope of one organization, but also applies and is needed by various organizations or companies and related parties such as supply chains and marketing by influencers, to achieve a common goal. With the alignment of objectives, the company is better prepared to face strategic risks and uncertainties.